Tracking soil resistance and virulence genes in rice-crayfish co-culture systems across China. (February 2023) - Du, Shuai; Feng, Jiao; Bi, Li; Hu, Hang-Wei; Hao, Xiuli; Huang, Qiaoyun; Liu, Yu-Rong
Graphical abstract: Highlights: RC model did not increase the abundance of soil resistance and virulence genes. Soil resistance and virulence genes had more connections with MGEs in RC system. Some human pathogens were potential hosts of soil resistance and virulence genes. Stochastic process drove the assembly of soil resistance and virulence genes. Bacterial community and MGEs primarily affected resistance and virulence genes. Abstract: Rice-crayfish co-culture (RC) has been widely and rapidly promoted as a sustainable agricultural system in many countries. The accumulation of crayfish residues could enhance soil organic matters; however, impacts of this integrated farming model on the dissemination and pathogenicity of resistance and virulence genes remain poorly understood. Here, we characterized antibiotic resistance genes (ARGs), biocide resistance genes (BRGs), metal resistance genes (MRGs) and virulence factor genes (VFGs) using metagenomic methods in paired RC and rice monoculture (RM) systems across China. The RC model did not increase the abundance of soil ARGs, BRGs, MRGs, or VFGs in comparison to the RM model, but selectively enriched 35 subtypes of these potential resistance and virulence genes. Network analysis revealed that resistance and virulence genes had a higher number of connections with mobile genetic elements (MGEs) in the RC system than that in the RM system, suggesting a higher horizontal transfer potential of these genes. Moreover, the RC model had a higher abundance of human opportunistic pathogens such as Salmonella enterica, Vibrio cholerae, and Shigella dysenteriae which were potential hosts of VFGs such as phoP, fleS, and gspE, suggesting a potential threat to human health. We further unraveled that stochastic process was the main driver of the assembly of resistance and virulence genes in the RC system. The abundance of ARGs and VFGs were primarily associated with microbial community compositions, while the abundance of BRGs and MRGs were mainly associated with that of MGEs. Taken together, our results suggest that the RC model has potential to cause the dissemination and pathogenicity of resistance and virulence genes, which has important implications for the control of soil-borne biological risks and the strategic management of sustainable agriculture.